Comparison between Adductor Pollicis and Orbicularis Oculi as Indicators of Adequacy of Muscle Relaxation for Tracheal Intubation Following Rocuronium Induced Neuromuscular Block: Randomized Comparative Clinical Trial - and Naveen G Singh, S.N. Suresh* (Recent Research in Science and Technology, 2010)
Background: The purpose of this study was to verify which muscle among the Adductor Pollicis (AP) and Orbicularis Oculi (OO) is a better predictor of optimal intubating condition after administration of Rocuronium. Methods: In this prospective, double blind, randomized study, 80 adult ASA –I and ASA – II undergoing general anaesthesia with tracheal intubation were allocated to two groups (n = 40) according to the reference muscle (AP or OO) used to determine the appropriate intubation time. Induction of anaesthesia was achieved with Inj Thiopentone 5mg/kg, Inj Fentanyl 2 mcg/kg and Inj Rocuronium 0.6mg/kg for muscle relaxation. Supramaximal Train Of Four (TOF–Guard acceleromyograph, neuro muscular monitor) stimulation of the ulnar nerve and facial nerve every 15 secs was used to monitor the neuromuscular block. After Train Of Four responses disappeared at Adductor Pollicis muscle or Orbicularis Oculi muscle, tracheal intubation and quality of intubation assessment was performed by an independent anaesthesiologist. Intubating conditions were scored on a Kreig et al scale. Results: Onset time at Orbicularis Oculi was significantly shorter than Adductor Pollicis muscle (P < 0.001), but adequate intubating condition were significantly increased in the Adductor Pollicis (Excellent – 87.5%, Good – 12.5%, Poor – 0%) compared with Orbicularis Oculi (Excellent – 27.5%,Good – 45%,Poor – 27.5%) after a dose of 0.6mg/kg of Rocuronium (P < 0.001) Conclusion: After administration of Rocuronium, twitch monitoring at Orbicularis Oculi allows a faster intubation but is associated with an unacceptable incidence of inadequate intubating condition . Adequate intubating conditions were observed with Adductor Pollicis muscle. Hence Monitoring neuromuscular activity of the Adductor Pollicis using Train of Four to determine the appropriate tracheal intubation time and condition is more clinically relevant than monitoring the Orbicularis Oculi muscle.